Unraveling the conditions for post-adoption contestation over hard climate policy in OECD countries - Ksenia V. Anisimova; James J. Patterson (npj Climate Action)
Abstract Understanding drivers of public contestation over hard climate policies is crucial for advancing climate action. While existing literature provides insights into conditions for policy support and adoption, conditions for policy contestation at the post-adoption stage remain opaque. We investigate conditions for policy contestation at the post-adoption stage in a sample of 27 national climate policies in OECD countries (2009–2022). We employ fuzzy-set Qualitative Comparative Analysis drawing on primary (62 structured expert interviews) and secondary (media, datasets, academic and grey literature, policy documents) data. Findings reveal that policy contestation arises from a combination of conditions, especially when policy is perceived as demanding and unfair, sometimes also combined with socio-political polarization, lack of climate change concern, and lack of information provision. This supports ex-ante work on expected conditions of contestation but also suggests a need for attention to conjunctural causation, complex socio-political constructs, and analyzing policy content and policy context jointly.